2021
DOI: 10.1002/pd.5934
|View full text |Cite
|
Sign up to set email alerts
|

The origins of aneuploidy research consortium

Abstract: The presence of high levels of aneuploidy in oocytes and early embryos and their fate is of considerable scientific and clinical importance. The Origins of Aneuploidy Research Consortium (OARC) was established to promote interdisciplinary communication and collaborative research into this topic. Under the umbrella of OARC, a series of papers has now been published in this Special Issue of Prenatal Diagnosis. Recent studies have transformed the view that aneuploidy is usually attributable to meiotic non‐disjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Mosaicism, known as partial aneuploidies, can be caused by postzygotic mitotic nondisjunction and may be associated with a less severe presentation, depending on the chromosome involved and the extent of cells affected presenting as a mosaic euploid/aneuploid line. Human implantation embryos in early development can present mosaic aneuploidies at a high frequency, with potential consequences for implantation and loss, and reconciling this finding with the embryo's ability to self-correct may pose a challenge in determining the clinical significance of the genomic imbalance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mosaicism, known as partial aneuploidies, can be caused by postzygotic mitotic nondisjunction and may be associated with a less severe presentation, depending on the chromosome involved and the extent of cells affected presenting as a mosaic euploid/aneuploid line. Human implantation embryos in early development can present mosaic aneuploidies at a high frequency, with potential consequences for implantation and loss, and reconciling this finding with the embryo's ability to self-correct may pose a challenge in determining the clinical significance of the genomic imbalance [10].…”
Section: Introductionmentioning
confidence: 99%
“…Much research had already been carried out in the area but it was fragmented within different disciplines such as embryology, epidemiology, and molecular biology. OARC brought together experts from these disparate areas and has already shown that the ‘whole is greater than the sum of its parts’ as Prenatal Diagnosis readers will have seen from the recent issue 18 . Not only did Eugene promote RGF and OARC, but he also provided the funds to run them.…”
mentioning
confidence: 99%
“…OARC brought together experts from these disparate areas and has already shown that the 'whole is greater than the sum of its parts' as Prenatal Diagnosis readers will have seen from the recent issue. 18 Not only did Eugene promote RGF and OARC, but he also provided the funds to run them.…”
mentioning
confidence: 99%